Trajetória Profissional E Intelectual De Manoel Cyridião Buarque No Ensino Paulista (Fins Do Século Xix E Décadas Iniciais Do Século Xx)" - Louro, Heloisa Amorim Pereira [UNIFESP] (2018)
The Present Work Deals With The Reconstruction Of The Professional And Intellectual Trajectory Of The Educator Manoel Cyridião Buarque (1860-1921) And Of His Role In The Construction Of São Paulo Education In The First Decades Of The 20th Century. He Arrived In São Paulo In 1889, Founded And Directed Establishments Of The Private Education Network That Gained A Reputation Over Time. He Entered At The Normal School Of São Paulo As A Lens In The Chair Of Psychology, Where He Worked From 1890 Until His Death In 1921. During His Career As A Professional Who Excelled In The Remodeling Project Of Escola Normal, Published Several Articles On Education, Teaching And Literature In The Most Renowned Newspapers That Circulated In The Beginning Of The Republic In The States Of São Paulo And Rio De Janeiro. He Participated In Networks Of Relations With Important Intellectuals Of The Time, And Served As Producer And Disseminator Of The Precepts Of The Renewed Pedagogy, Being One Of The Educators Responsible For The Moderni